2015
DOI: 10.1017/s1742170515000162
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the social and economic benefits of organic and fair trade tea production for small-scale farmers in Asia: a comparative case study of China and Sri Lanka

Abstract: Organic agriculture has the potential to provide improved livelihood opportunities, increased income and social benefits for resource-poor small-scale farmers. It has thus become a popular strategy for economic development and poverty reduction in many areas of the global south. However, there has been limited empirical research regarding the actual benefits of certified organic production, particularly when organic is combined with fair trade certification, and for small-scale farmers who are not engaged in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 22 publications
(43 reference statements)
0
55
0
Order By: Relevance
“…The same study region is reported in (Rueda and Lambin 2013) and . b One paper (Qiao et al 2016) includes two study areas for tea. which farmers undertake to maintain options for different markets.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…The same study region is reported in (Rueda and Lambin 2013) and . b One paper (Qiao et al 2016) includes two study areas for tea. which farmers undertake to maintain options for different markets.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Chiputwa et al (2015) argue that although consumers in the developed countries are willing to pay significant price premiums for organic food which meets sustainability standards, how effectively these benefits reach the producing countries especially the farmers in the poor countries (e.g., Uganda and Ethiopia) is unknown. According to Qiao et al (2016) although the price premiums could compensate for some extra costs, among other factors, smaller plot sizes in poor countries inhibit gaining all the benefits of organic food production. This definitely indicates an area of further investigation.…”
Section: Organic Food Consumption As a Sustainability Movementmentioning
confidence: 99%
“…Organic Agriculture goes far beyond organic food certifications as it addresses the issues such as food insecurity, land degradation, poverty, and climate change (IFOAM, 2017a). Thus, it has become a strong contributor to sustainable development at a larger scale (Qiao et al, 2016).…”
mentioning
confidence: 99%
“…Finally, OF has the potential for both mitigation and adaptation strategies, both of which enhance the environment's resilience to climate change [46]. Studies show that farmers are able to obtain various economic benefits from OF, such as saving money through the reduction of input cost by substituting chemical inputs with locally available organic inputs [52]. They can also increase their income through the sale of their byproducts and by entering organic markets with certified products and selling their products at premium prices [23].…”
Section: Organic Farmingmentioning
confidence: 99%